Effect of BaCO3 addition on critical temperature of Bi-Pb-Sr-Ca-Cu-O superconductor. Issue 1 (May 2021) - Akbar, I A; Imaduddin, A; Humaidi, S; Nugraha, H
Abstract: Bi-Pb-Sr-Ca-Cu-O high temperature superconductor has been applied in the field of electricity as power transport cables. This work has been carried out to investigate the effect of addition of BaCO3 on Bi1, 6 Pb0, 4 Sr2 Ca2 Cu2 O10 superconductors. Solid state reaction method was used to prepare all samples. The starting materials were Bi2 O3, PbO2, SrCO3, CaCO3, CuO, and BaCO3 powder. Starting materials without BaCO3 were ground using a mortar agate for 3 h. After calcination process of 820°C for 20 h, samples were mixed with BaCO3 (1 %wt, 2 %wt) and then sintered by 850°C for 30 h. Characterizations ware conducted by using cryogenic magnet to determine the critical temperature (Tc), SEM-EDX to analyze morphology, and XRD to determine the phase formed. There were semiconductor properties at high temperature and it was found that the addition of BaCO3 decreased Tc of the samples. 1 %wt BaCO3 showed a critical temperature with Tconset = 86 K and Tczero = 52 K, and 2 %wt of BaCO3 has Tconset of 80 K, and Tczero of 23 K. The surface morphology contains agglomeration and there is a lot of porosity. The dominant phase formed is Bi(Pb)-2212 with a volume fraction of 64.71%.